2011
DOI: 10.1007/s12070-011-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Patients of Chronic Renal Failure: A Study of 100 Cases

Abstract: The purpose of our study was to determine the incidence of hearing loss and to describe the hearing impairment and the possible contributing factors, responsible for sensori neural hearing loss in chronic renal failure (CRF) patients. This was a prospective study carried out on 50 cases of CRF attending otorhinolaryngological services for hearing disturbance and on 50 healthy volunteers for control study, having the same inclusion criteria except (does not suffering with CRF) having normal renal function tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 9 publications
6
42
0
3
Order By: Relevance
“…[19] Similarly, Yassin et al found a correlation between hearing loss and hyponatraemia and suggested the possibility of a common defect in membrane transport of ions. [20] In our study, we found that both hyponatraemia and hypokalaemia has an association with hearing loss group, but association of hyponatraemia is more stronger than hypokalaemia.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…[19] Similarly, Yassin et al found a correlation between hearing loss and hyponatraemia and suggested the possibility of a common defect in membrane transport of ions. [20] In our study, we found that both hyponatraemia and hypokalaemia has an association with hearing loss group, but association of hyponatraemia is more stronger than hypokalaemia.…”
Section: Discussionsupporting
confidence: 43%
“…[21] Though the role of dialysis is unclear, adverse factors possibly related to haemodialysis are acute hypotension, reduction in blood osmotic pressure, acute clearance of urea, increased red blood cell mass and immunologic reaction to dialyzer membranes. [22] Further, it has been proposed that long-term haemodialysis may cause electrolyte, osmotic and biochemical alterations leading to sensorineural hearing loss, [20] though a single session may not have significant effect on hearing. In a study by Erkoc et al, the mean duration of haemodialysis in the patient group with hearing loss was longer than that in the patient group without hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients reported within a mean [16]. Hearing assessment in normal Indian adults (\60 years of age) with no risk factors for hearing loss show the prevalence of sensorineural hearing loss to range from 0 to 6 % [21,22] and males comprising two-thirds of them [21]. The 78 % prevalence of hearing loss in pSS noted in our study with predominantly female population, therefore, does not reflect the commonly prevalent scenario of hearing impairment in the normal Indian population.…”
Section: Discussionmentioning
confidence: 71%
“…10,11 Notably, many older studies have shown higher prevalence of hearing loss, possibly due to small sample sizes. Hearing thresholds were abnormal at high frequencies in 77.5 per cent of CKD patients and at low frequencies in 27.5 per cent in our study.…”
Section: Discussionmentioning
confidence: 99%